ANALISIS KOEFISIEN ABSORPSI DARI MATERIAL BERBAHAN DASAR LIMBAH KAIN PERCA DAN PELEPAH PISANG - Patricia P. Noviandri; Centaury Harjani; Adindra M. K. Astuti (ATRIUM: Jurnal Arsitektur, 2020)
Title: Coefficient Absorpsi Analysis from Patchwork Material and Banana Midrib Preliminary research related composite waste material and nature has done. This research continues the previous research with a more accurate testing method using impedance tubes. Material samples made in this study are samples that have a greater NR (Noise Reduction) value in previous studies. Material samples were made as many as 4 samples with different substance variables, namely fine composite samples, rough composites, banana midrib, and combinations (fine composites and banana midrib). Three samples were mold using a tube with a diameter of 30 mm and a height of 70 mm while one sample combination was a material that was combined to reach a height of 50 mm. From the test results, the addition of cavity affects the absorption coefficient value, therefore the use of this material in buildings must use an air cavity so that the absorption coefficient value increases. Samples that have character as sound absorbing material are fine composite materials, banana fronds, and combination materials because they have an absorption coefficient value (?) of more than 0.30. The combination material has the highest NRC value among the other samples that is equal to 0.57.